Minor head trauma in football and serum levels of S100B - Straume-Naesheim, T.; Andersen, T. E.; Jochum, M.; Dvorak, J.; Bahr, R. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Background: It has been suggested that heading and head traumas in football can cause brain impairment. The protein S100B is a marker of acute neuronal tissue damage. Objective: To compare the serum concentration of S100B after a head trauma to the effect of heading, high-intensity exercise and playing a regular league match (without head trauma). Method: Baseline serum levels of S100B were measured for players in the Norwegian elite league (86.0% participation, N=535). Of a total of 228 head impacts registered during two football seasons, 65 impacts were followed up with blood sampling one hour after the impact (B1) and 40 the following morning (B12). A control group of 49 players without a head trauma were followed up with the same procedure after a match (Match Control). In addition, three teams (N=48) performed a high-intensive exercise session without heading and a low-intensity training session with heading exercises. The serum levels of S100B were measured before the first training session and within 1 (B1) and 22 (B12) hours after each of the training sessions. Results: All groups showed a transient increase in serum S100B from baseline to B1. There was a significant difference between the joint match groups (Head Impact and Match Control) and the joint training groups (High-Intensity Exercise and Heading) both in absolute values and delta values at B1, but no differences at B12 (B1: Match=0.10 [95% CI: 0.090 to 0.11] ng/ml, Training=0.071 [95% CI: 0.065 to 0.077] ng/ml, p<0.001, Delta B1: Match=0.062 [95% CI: 0.052 to 0.073] ng/ml, Training=0.026 [95% CI: 0.020 to 0.031] ng/ml, p<0.001). However, there were no significant differences in B1 or delta B1 between the Head Impact and Match Control groups, nor between the High- Intensity Exercise and Heading groups. In the joint training group, 5 (5.8%) players showed elevated B1 values (i.e. above an established cut-off of 0.12 ng/ml) compared to 39 (33.9 %) in the joint match group (Chi square, p<0.001). However, there was no difference in the prevalence of elevated B1 values between the Match Control Group and the Head Impact Group. Conclusion: The serum levels of S100B are increased after both football training and football matches. There is a possible additive effect of activity with high intensity and heading, but minor head impacts do not seem to cause an additional increase. Consequently, there is no evidence suggesting that there is significant brain tissue injury after minor head impacts in football.